PENYULUHAN PENCEGAHAN TERHADAP PERMASALAHAN NYERI LUTUT PADA PETANI DI POSYANDU LANSIA MELATI 3 DESA GENTAN - Pristianto, Arif; Furqony, Ifrah Yaumil; Prahesti, Yona Risha; Selandani, Ajeng Adela; Putri, Risma Salsabila Isnaini (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Osteoarthritis is a degenerative joint disease in which there is damage to the cartilage which causes pain and loss of movement ability. Risk factors for OA include age, gender, obesity, trauma or injury, muscle and ligament weakness in the knee. Because many members of the community did not know about the symptoms of OA, we therefore held outreach to the people in Gentan village. The method of carrying out the activities that the author does is the educational outreach method with lectures and simulation training, using PowerPoint media. Results: In providing education and simulation training, it was found that 95% understood material related to knee pain and osteoarthritis, and 59.1% of participants stated that the exercises carried out had an effect on the knee pain they experienced. The activities carried out are very effective in increasing the knowledge of at-risk workers, especially farmers, regarding knee pain they experience and exercises that can be done when they feel knee pain.